OR20-01 AMH Preserves Fertility in Chemotherapy-Treated Mice Through a Mechanism Involving Autophagy - Beau, Isabelle (J Endocr Soc, 2020)
Chemotherapy-induced ovarian failure and infertility is an important concern in female cancer patients. The follicular ovarian reserve is established early in life then keeps declining regularly along reproductive life. This reserve is constituted by dormant primordial follicles (PMF) which are necessary to maintain female reproductive function. There is a continuous repression of PMF activation in early growing follicle through the balance between factors activating the initiation of follicular growth, mainly actors of the phosphatidyl-inositol-3-kinase (PI3K) signaling pathway, and inhibiting factors such as Anti-Müllerian Hormone (AMH). Any alteration of this equilibrium may induce early follicle depletion and subsequent infertility. Cyclophosphamide (Cy) one of the alkylating agents commonly used for treating breast cancer is able to trigger PMF activation further leading to premature ovarian insufficiency. Preventing chemotherapy-induced ovarian dysfunction might represent an option for preserving optimal chances of natural or medically assisted conceptions after healing. We showed in a model of Cy-treated pubertal mice, that AMH administration was able to restrain PMF depletion by counting the total PMF number within mouse ovaries. Moreover, the PI3K signaling pathway was evaluated following Cy administration with and without AMH injection. We showed that AMH decreased the phosphorylation of FOXO3A, a transcription factor of PMF activation and induced its nuclear translocation. Altogether, the results support a protective role of AMH against Cy-induced follicular loss. To better understand AMH action in the ovary, we investigated the molecular mechanism to explain the protective effect of this hormone on the PMF pool. It has been reported that autophagy, a lysosomal degradative ubiquitous process implicated in cellular homeostasis, was involved in both ovarian follicular death and survival mostly by PI3K pathway (Gawriluk et al. Reproduction 2011 141, 759–765). We show in mice that Cy inhibits autophagy in the ovary while AMH induces autophagy. In vivo analysis of autophagic flux is currently in progress to dissect this process more finely. Interestingly, FOXO3A was shown to be related to autophagy activation. To investigate the role of FOXO3A in AMH-induced autophagy further, we analyzed mRNA and protein expression of autophagy-related genes controlled by FOXO3A, including BECLIN-1, ATG12, ULK1, BNIP3, GABARAP, and LC3B. These findings establish a close relationship between AMH and autophagy to protect PMF stockpile and to limit follicular depletion induced by Cy.